2014
DOI: 10.1080/17501229.2014.882929
|View full text |Cite
|
Sign up to set email alerts
|

Urban adolescent students and technology: access, use and interest in learning language and literacy

Abstract: Adolescents today have vastly different opportunities to learn and process information via pervasive digital technologies and social media. However, there is scant literature on the impact of these technologies on urban adolescents with lower socioeconomic status. This study of 531 urban students in grades 6-8 used a self-reported survey to collect information about (1) students' access to and frequency of using desktop, laptop and tablet computers, and mobile phones, (2) their ownership of mp3 players, iPods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
(11 reference statements)
2
23
0
Order By: Relevance
“…However, this research shows that if the time spent watching TV increases students' self-efficacy regarding all their verbal communication skills are negatively affected. It is known that digital technologies, social media, and time spent in virtual environments and using software applications are attractive to young people and can provide extensive education opportunities across different times and distances [26]. However, in their studies of university students Stankovska, Angelkovska, and Grncarovska, suggest that overuse of the internet may lead to poor performance at school, social isolation, depression and loneliness, and they determined a potential negative relationship between internet use and loneliness (r = .009, p> .01); and between internet addiction and high academic performance (r = .002, p> .01) [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, this research shows that if the time spent watching TV increases students' self-efficacy regarding all their verbal communication skills are negatively affected. It is known that digital technologies, social media, and time spent in virtual environments and using software applications are attractive to young people and can provide extensive education opportunities across different times and distances [26]. However, in their studies of university students Stankovska, Angelkovska, and Grncarovska, suggest that overuse of the internet may lead to poor performance at school, social isolation, depression and loneliness, and they determined a potential negative relationship between internet use and loneliness (r = .009, p> .01); and between internet addiction and high academic performance (r = .002, p> .01) [27].…”
Section: Discussionmentioning
confidence: 99%
“…The reported recreational and relaxation benefits associated with iPods have clearly created a new culture infused with music among college students (Hoover, et al, 2010). In the recent research of Li (2015), findings indicate a widespread use of computers, cell phones, and social media, as well as frequent access to the internet among urban adolescents from lower social economic status families. About 70% of the respondents used cellphones on a daily basis, and over 55% used desktop and laptop computers every day or at least once every 2-3 days.…”
Section: Perceived Ease Of Use Of Computer Applications and Frequencymentioning
confidence: 99%
“…Group differences in technology adoption associated with age have been reported among youth. A self-report survey conducted among 531 middle school students showed that 8 th graders (14year-olds) reported significantly more access, more frequent use, higher levels of ownership of technology devices and social media accounts than 6 th and 7th graders (12-13 year olds) (Li, Snow, & White, 2014). Livingstone and Helsper's (2007) study with 1,511 students aged 9-19 in the U.K. showed 74% of them had Internet access at home.…”
Section: Technology Use and Teen Culturementioning
confidence: 99%
“…A study of 518 Belgian 16-to 19-year-old students also showed that "socioeconomic status affects computer ownership only moderately" (Van Braak & Kavadias, 2005, p. 43). Our recent survey study with 531 middle school students aged between 12 and 14 in a U.S. public school located in a lower income neighborhood also revealed that the digital divide related to social economic status (SES) is disappearing, as these low-income urban teens' access to technology devices was comparable to that in the general teen population (Li, Snow, & White, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation